Household Financial Access and Risk Sharing in Nigeria - Carlson, Stacy; Dabla-Norris, Era.; Saito, Mika.; Shi, Yu. (Washington, D.C. : International Monetary Fund, 2015)
We examine the role of household financial access in determining the extent of risksharing in Nigeria using household-level panel data. We estimate changes in the response of consumption to shocks for households with formal and informal access to finance and those without, both for the country as a whole and for different regions. Our findings suggest that households with financial access who experience an unexpected negative income shock see consumption fall by 15 percentage points less than those without access. This result is mainly driven by households with informal financial access, and by household savings rather than borrowing. Regional variation in risk sharing tends to be significant, suggesting that financial inclusion efforts going forward should have a more regional focus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet